2015
DOI: 10.20473/ijosh.v4i1.2015.1-10
|View full text |Cite
|
Sign up to set email alerts
|

Studi Faal Paru Dan Kebiasaan Merokok Pada Pekerja Yang Terpapar Debu Pada Perusahaan Konstruksi Di Surabaya

Abstract: Dust exposure received by workers can affect workers’s pulmonary function and health condition affected by many factors. This observation conducted on construction. The purpose of this research was identify description about pulmonary function and smoking habit at construction workers. Researcher used cross sectional study. The sample of this research was total population of finishing workers as much as 18 workers who doing construction project in Surabaya . Measurement of dust concentration conducted on three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
0
10
0
3
Order By: Relevance
“…long periods of time can lead to many lung diseases that were adapted to lung conditions. [10] In the results of the Chi-Square statistical test, Pearson scores were obtained with a 95% significance level of 0.013 (p <0.05). It can be concluded that there is a relationship between nutritional status and lung function capacity in metal coating workers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…long periods of time can lead to many lung diseases that were adapted to lung conditions. [10] In the results of the Chi-Square statistical test, Pearson scores were obtained with a 95% significance level of 0.013 (p <0.05). It can be concluded that there is a relationship between nutritional status and lung function capacity in metal coating workers.…”
Section: Resultsmentioning
confidence: 99%
“…Workers are exposed to chromium through inhalation. Inhalation of short-term exposure to chromium (IV) can cause respiratory problems such as shortness of breath, coughing, sneezing, septal perforation and ulceration, bronchitis, decreased lung function, pneumonia, asthma, itching and pain in the nose 10 while in the long term can cause pulmonary fibrosis and lung cancer 11…”
Section: Resultsmentioning
confidence: 99%
“…Also, nicotine will kill the cilia's function, ultimately causing obstructed airway clearance (33). The more prolonged the smoking habit, the more sediment there is in the lungs so that the air passages to enter and exit become narrower (34).…”
Section: Smoking Habitmentioning
confidence: 99%
“…There are six people of Besole village marble workers who wear PPE when working (25%) and 18 people who do not wear PPE (75%). Adherence to PPE use is a preventive factor that results in a decrease in lung function capacity (22,30,32). Workers who obey the habit of wearing masks will minimize inhalation exposure while breathing (33).…”
Section: Analysis Of the Characteristics Of Marble Workers On Lung Comentioning
confidence: 99%